2019
DOI: 10.1111/aor.13398
|View full text |Cite
|
Sign up to set email alerts
|

A novel power supply system for puborectalis‐like artificial anal sphincter

Abstract: Puborectalis‐like artificial anal sphincter (PAAS) is an innovative new type of artificial anal sphincter (AAS). It overcomes many drawbacks and inadequacies of various previous AASs, and it has successfully been implanted in vivo for almost 3 weeks. During in vivo testing, PAAS shows its ability to retain continence with low risk of ischemia necrosis, and somehow truly helps to remodel rectal perception. However, there are still many defects that influence the long‐term implantation of PAAS, especially in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Zerun Zhou et al of Shanghai Jiao Tong University, Shanghai, China reported on a puborectalis‐like artificial anal sphincter (PAAS) implanted for almost 3 weeks. It showed the ability to retain continence with low risk of ischemia necrosis.…”
Section: Bioengineering and Biomaterialsmentioning
confidence: 99%
“…Zerun Zhou et al of Shanghai Jiao Tong University, Shanghai, China reported on a puborectalis‐like artificial anal sphincter (PAAS) implanted for almost 3 weeks. It showed the ability to retain continence with low risk of ischemia necrosis.…”
Section: Bioengineering and Biomaterialsmentioning
confidence: 99%
“…It helps patients regain continence by the attraction force of the magnetic beads. MAS is a method used to improve the quality of life of patients with severe fecal incontinence 8 . However, its work depends on the magnetic force, which may cause constipation if beads cannot be separated by force, 9‐11 not at the will of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…MAS is a method used to improve the quality of life of patients with severe fecal incontinence. 8 However, its work depends on the magnetic force, which may cause constipation if beads cannot be separated by force, [9][10][11] not at the will of the patient. And the effectiveness for liquid excrement is not good as expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in prior in vivo experiments, it was shown that hyperplasia wrapped the nylon-12 rotatable arm and caused mechanical failure, approximately 2 months after implantation. [5][6][7][8][9] Thus, although the PAAS improves many defects which occurred in previous AAS systems, it is limited by the influence of hyperplasia. Accordingly, there are still obstacles in the application of the system in clinical practice.…”
Section: Introductionmentioning
confidence: 99%